BizTalk 2010 Recipes - Beckner, Mark (Apress, 2012)
BizTalk 2010 has a number of new features that will aid developers and increase the ability of the platform to support solutions built on it. The primary updates center around the BizTalk mapper user interface and EDI trading partner configuration and management. Additional updates include improvements to administrative functionality and the consolidation of tools within the BizTalk Admin Console. The recipes in this chapter are meant to introduce this new functionality.